Broad-range polymerase chain reaction and sequencing for the diagnosis of infectious diseases - Nicole E. Putnam; Drew W. Charles; James B. Doub; J. Kristie Johnson (Microbiology Spectrum)
ABSTRACT Broad-range polymerase chain reaction (BR-PCR) identifies molecular signatures of microorganisms directly from clinical specimens without requiring microbial growth in culture. BR-PCR may be a powerful tool to reveal microbial causes of infectious diseases, but the impact on diagnosis and clinical management has yet to be fully defined. Consequently, the aims here were to investigate how bacterial, fungal, and mycobacterial (AFB) BR-PCR perform compared to microbiology culture methods in detecting microorganisms and to assess clinical utility, defined as the ability of the results to change antimicrobial therapy or treatment duration. Between 2018 and 2021, 348 unique specimens were sent from 327 patients seen within the University of Maryland Medical System (UMMS). Patient charts were reviewed retrospectively. Organisms identified by BR-PCR were compared to bacterial (n = 302), fungal (n = 137), and AFB (n = 111) cultures to determine concordance and were evaluated to determine if they led to a change in clinical management. Agreement in organism(s) reported by BR-PCR and culture was considered concordant for calculating performance data. Sensitivity of BR-PCR compared to concordant culture results was 30.9% for bacteria (25/81; 95% CI: 21.8–41.6%), 18.8% for fungi (3/16; 95% CI: 5.8–43.8%), and 33.3% for AFB (1/3; 95% CI: 5.6–79.8%) detection. The bacterial negative percent agreement of 80.1% (165/206) may reflect antibiotic pretreatment or detection of fastidious organisms. Despite longer turnaround times, BR-PCR results changed clinical care in 6% of cases. Based on these findings herein, the clinical use of BR-PCR would be best utilized when fastidious organisms are suspected, or specimens remain culture negative, but should not replace routine culture methods at this time.IMPORTANCEDetermining infectious etiology can be challenging in patients with chronic presentation and in those receiving empiric therapy. In addition to the standard of care (microbiology cultures), providers can order a broad-range polymerase chain reaction and sequencing (BR-PCR) test to identify microorganisms directly from clinical specimens and independently from culture. While studies have been done from individual hospitals or systems, there is a lack of broadly applicable clinical evidence detailing clinical scenarios in which BR-PCR should be utilized. This study adds to the growing body of literature surrounding BR-PCR clinical usage, examining assay performance and clinical utility of BR-PCR test results. Although BR-PCR and culture had low concordance among organisms identified, it was shown to complement the standard of care for uncommonly isolated and fastidious organisms. Overall, BR-PCR results changed clinical management in 6% of cases, which is similar to other studies that include a broad representation of specimen types.